2018
DOI: 10.4067/s0717-75182018000200032
|View full text |Cite
|
Sign up to set email alerts
|

Una mirada actualizada de los beneficios fisiológicos derivados del consumo de legumbres

Abstract: Las legumbres han sido históricamente consideradas una apetecible fuente de proteínas y fibra. En estos tiempos caracterizados por una tendencia epidemiológica al sobrepeso y a la obesidad, corregir hábitos poco saludables es prioritario. La incorporación de legumbres al menú cotidiano como sustituto de carnes podría significar, a mediano y largo plazo, aminorar la prevalencia de enfermedades crónicas no-transmisibles. Este trabajo ofrece una mirada actualizada de algunos constituyentes claves presentes en las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
1
0
0
Order By: Relevance
“…In the case of C. arietinum, the slight loss of activity after the cooking process may be associated with partial inactivation of the proteins present in C. arietinum. These results resemble the findings of Hidalgo et al (2018), who demonstrated that cooking affects the protein content of chickpeas. Regarding the inhibition percentage, our results are similar to those obtained by Chávez-Ontiveros et al (2022), who evaluated the effect of extrusion on protein hydrolysates from this seed subjected to digestion in an enzymatic system (α-amylase-pepsin-pancreatin),…”
Section: Discussionsupporting
confidence: 89%
“…In the case of C. arietinum, the slight loss of activity after the cooking process may be associated with partial inactivation of the proteins present in C. arietinum. These results resemble the findings of Hidalgo et al (2018), who demonstrated that cooking affects the protein content of chickpeas. Regarding the inhibition percentage, our results are similar to those obtained by Chávez-Ontiveros et al (2022), who evaluated the effect of extrusion on protein hydrolysates from this seed subjected to digestion in an enzymatic system (α-amylase-pepsin-pancreatin),…”
Section: Discussionsupporting
confidence: 89%
“…Flavonoids are the primary source of phenolic compounds and are associated with important health benefits [93]. The primary polyphenols found in beans are flavonoids, and their chemical nature has been extensively studied [94]. The content of total polyphenols and flavonoids has been quantified in beans and it ranges between 0.1 to 3.8 mg (mg GAE/g DW) and 0.2 to 7.0 mg (mg RE/g DW).…”
Section: Cofactors For Collagen Biosynthesismentioning
confidence: 99%
“…On the other hand, as legume production at the local level has decreased significantly in the last 30 years, the Chilean consumption of legumes is quite satisfactory despite this local scenario. In a systematic study on the changes experienced in dietary patterns between 1990 and 2010 conducted in 187 countries, Chile ranked among the top 10 countries consuming pulses, averaging 25-30 grams per day [9]. In addition, the results of the National Food Consumption Survey (ENCA) showed that the average daily intake observed was 17 g/day, with an increase to 21.8 g/day in rural areas, with the most significant consumption in the Central-South Region of the country (25.9 g/day) [10].…”
Section: Introductionmentioning
confidence: 99%